Design, Validation, and Analysis of Perceived Sign Usability Scale Vis-à-vis Cognitive Sign Characteristics - Donald, Stephen (Universiti Malaysia Sarawak (UNIMAS), 2018)
This study was galvanized by the lack of instruments to assess users’ perception on sign usability. This study introduces Perceived Sign Usability Scale (PSUS), which is an instrument to assess sign usability pertaining to its cognitive sign characteristics (CSC). This study delineates the process of designing and developing the PSUS. The design of the instrument involves the development of items as well as a formula to calculate the composite score of PSUS. PSUS utilizes an open-ended sign comprehension test and Likert-type items to assess sign usability. The combination of both methods results in a more intuitive and valid instrument. This study adapts statistical methods such as the c-coefficient, Multiple Responses Analysis, Cochran’s Q with Pairwise McNemar as post-hoc tests, as well as Rasch Analysis. This study has the potential to spearhead the emergence of sign usability studies both locally and internationally because of the identification of CSC, the introduction of PSUS, design framework/technique, as well as the derivation of formula to calculate the composite score of Likert-type items. Although PSUS is proved to be valid and reliable, it is still subjected to inevitable limitations. PSUS may not cover the complete extent of sign usability because it is an indubitable fact that human cognition and sign usability are complex. There could be more CSC emerged in the future to be integrated into the new version of PSUS. However, this limitation is not undesirable as it also serves as a catalyst that allows for continuous improvement of the instrument.